Effect of additional fertilizer and pruning on growth of pointed gourd (Bangladesh Journal of Agricultural Research, 2008)
The experiment was conducted at the Regional Agricultural Research Station, Ishurdi, Pabna during the growing season of 2001-2002 and 2002-2003 to investigate the different levels of pruning and application of additional fertilizer on the growth and yield of pointed gourd. The highest yield (28.17 t/ha) was recorded by additional fertilizer treatment. Pruning intensities differed significantly in respect of different yield contributing characters and yield. The highest yield (34.54 t/ha) was recorded in medium pruned plants, while the lowest yield (19.06 t/ha) was recorded in heavy pruned plant. The highest yield was recorded in crops receiving additional fertilizer and medium pruning and the lowest yield was observed in crop receiving no additional fertilizer with heavy pruning. The highest benefit cost ratio (3.66) was obtained from additional fertilizer with medium pruning treatment.Bangladesh J. Agril. Res. 32(4) : 565-571